2005
DOI: 10.1038/sj.eye.6701955
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of blindness related to smoking: a hospital-based cross-sectional study

Abstract: Aims Smoking is associated with several serious eye diseases. Awareness of smoking and blindness, and its potential to act, as a stimulus to assist stopping smoking has not been investigated. Methods A cross-sectional survey using a structured interview of adult patients attending district general hospital ophthalmology, general surgery, and orthopaedic clinics. The interview investigated the awareness and fear of blindness for three established smokingrelated diseases, and a distractor condition (deafness), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 3 publications
6
41
2
Order By: Relevance
“…Our study in an Asian population yielded results similar to that of Bidwell et al 4 and Moradi et al; 5 in that the motivation score to quit smoking due to irreversible central blindness was the second highest among all the conditions examined, following only lung cancer. Hence, despite a low level of awareness, blindness is still a significant motivational factor for smoking cessation.…”
supporting
confidence: 79%
See 3 more Smart Citations
“…Our study in an Asian population yielded results similar to that of Bidwell et al 4 and Moradi et al; 5 in that the motivation score to quit smoking due to irreversible central blindness was the second highest among all the conditions examined, following only lung cancer. Hence, despite a low level of awareness, blindness is still a significant motivational factor for smoking cessation.…”
supporting
confidence: 79%
“…A hospital-based cross-sectional survey of patients in the United Kingdom revealed that only 9.5% of patients believed that smoking was definitely or probably a cause of blindness, compared with 70.6 to 92.2% for stroke, heart disease and lung cancer. 4 A survey of teenagers aged from 16 to 18 years in the United Kingdom yielded similar results. 5 However, despite the low level of awareness of smoking-related blindness found in these studies, the fear of blindness was as compelling a motivation for smoking cessation, if not more, as the fear of lung cancer, heart disease, and stroke.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Older participants were less likely to try quitting and less likely to attend a smokers' quit session. Knowledge of the link between smoking and eye disease (46.9%) is much higher than previous studies which found 9% of the UK adult 28 and 5% of the teenage population 29 were aware of the link. A survey from Singapore found only 7.3% of their population knew of the link.…”
Section: Outcomes Of Experimental Groupscontrasting
confidence: 44%